Photocatalytic Reactions of a Nickel(Ii) Annulene Complex Incorporated in Polymeric Structures - Costamagna-Martra, J; Costamagna-Martra, J (Royal Society of Chemistry, 2014)
The photochemical reactions of the Ni(II) annulene complex, [NiII([5,7,12,14]-tetra methyl dibenzo[2,3-b:2,3-b,i][1,4,8,11]tetraaza[14]annulenate)], grafted into a poly(isobutylene-alt-maleate) backbone were investigated in aqueous media. The grafted Ni(II) complex becomes soluble in aqueous and organic solvents where the strands form aggregates with medium-dependent shapes. Irradiation of the polymer at 532 or 351 nm produce charge-separated macrocyclic pendants, CS, with a lifetime ? ? 30 ns. CS reacts with electron donors and acceptors before it decays with a lifetime ? ? 1 ?s. In parallel to the decay of CS, an excited state-excited state annihilation process gives rise to luminescence whose spectrum spans wavelengths shorter than the wavelength of the irradiation, ?ex > 500 nm. Theoretical calculations were carried out with the aim of understanding the morphology and structures of strand aggregates, to confirm the nature of reaction products and to account for the spectroscopic and photochemical properties of the Ni(II) pendants. The endothermic reduction of CO2 to CO by S(IV) species was used as a test of the Ni(II) complex s ability to photocatalyze the reaction. In the photoprocess, the Ni(II) complex fulfills the double role of antenna and catalyst. © the Partner Organisations 2014.